Scientific reasoning of the connection between the conceptual positions of the social responsibility theory and the social management elements of the pharmaceutical organization - Tkachenko, N. O.; Hromovyk, B. P.; Ткаченко, Наталя Олександрівна; Громовик, Б. П. (Research Journal of Pharmaceutical, Biological and Chemical Sciences, 2018)
The purpose of the work was the scientific reasoning of the connection between the conceptual positions of the social responsibility (SR) theory and the social management elements of the pharmaceutical organization. Publications of fundamental and applied researches of national and foreign scientists on social responsibility issues, social investment, human capital (HC) were used for the research. Methods of informational search, systematization, analysis, synthesis, comparison, generalization and modeling were used during the work. The interrelation between the forms and practices of SR as an element of social management with the conceptual positions of social investment theories and HC for pharmacy was justified on the basis of the scientific analysis. The most important indicator of SR is conscious and purposeful participation in solving important social problems through social investments. HC of pharmaceutical organization is formed due to the labor market and the system of continuous pharmaceutical education, and investment in HCs is a long-term factor of competitiveness and survival of the pharmaceutical organization. At the same time, social investments are considered as the main source of profit in the future and as the highest form of SR pharmaceutical organization. The pharmaceutical organization can ensure its effective and competitive existence by forming social capital, developing SR and social management by coordinating own interests with the system of interests in society.
Keywords: social responsibility; pharmaceutical organization; social investment; human capital